Peran ASEAN dalam Krisis Kemanusiaan Pasca Kudeta Militer Myanmar pada Tahun 2021 - Nau, Novriest Umbu Walangara; Jekaisa, Heyna; Priscilla, Sherin Natasya (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 1 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONALDO - 10.24843/JIWSP.2023.v05.i01.p05, 2023)
This research discusses ASEAN's role in the humanitarian crisis after the Myanmar military coup during the Covid-19 pandemic. Myanmar's position in the midst of a coup d'état amid Covid-19 has greatly impacted people's lives in Myanmar, which have become a victim caused from military regime and the spread of Covid-19. The focus of this research is first, the role of ASEAN as a Southeast Asian regional organization after the Myanmar coup. Second, the form of assistance provided by ASEAN to Myanmar. Third, ASEAN's obstacles in solving problems in Myanmar. The research method used is qualitative through literature studies, which found that the principle of ASEAN non-intervention is one of the major challenges for ASEAN. Nevertheless, ASEAN continues to actively play a role by providing humanitarian assistance to combat the spread of Covid-19 such as medical equipment and medicine assistance to Myanmar to help victims after the coup and Covid-19. Key Words: ASEAN, Humanitarian Aid, Myanmar, Non-intervention.